Predictors of Helping Behavior on Smoking Cessation among Nursing Students - Pungbangkadee, Rudee; Chaiyasung, Phatcharaphan; Ruamsook, Tanawat (Journal of The Royal Thai Army Nurses, 2023)
This research is a descriptive study aimed to examine the smoking cessation helping behavior among nursing students and to explore factors predicting smoking cessation helping behavior of nursing students. The study was based on five factors of health literacy: accessibility skills, comprehension skills, questioning skills, decision-making skills, and application skills. The purposive sampling was 688 nursing students at nursing Institutes. The instruments were a questionnaire of heath literacy in smoking cessation helping and smoking cessation helping behavior. The Content Validity Index (CVI) was .92 and the Cronbach’s alpha coefficient were .92 and .96 respectively. The data were analyzed by mean, standard deviation, Pearson’s Product Moment Correlation Coefficient and Stepwise Multiple Regression Analysis. The results revealed that the samples had 5 factors of health literacy were at a high level ( = 3.31, SD = .47). The smoking cessation helping behavior were at a moderate level ( = 2.87, SD = .64). The application skills (r=.50) and questioning skills (r=.45) predicted the smoking cessation helping behavior of nursing students by 27.4 percent (R2 = 0.27, F= 129.05). The recommendation develops a skills-building program that encourages knowledge of smoking cessation so that students have the attributes of being more literacy in smoking cessation.